Impact of Old Age Allowance on Socio-Economic Well being of Elderly People in Pokhara - Ranabhat, Deepesh (Journal of Development and Social Engineering, 2022)
This study aims to examine the impact of old age allowance on socio-economic wellbeing of elderly people in Pokhara. For this purpose, out of total 630 recipients of old age allowance in Pokhara Metropolitan-26, 135 respondents have been purposively selected. Information was collected from these respondents using structured questionnaire. Both descriptive as well as inferential statistics were used for the analysis. The mean score analysis shows that old age allowance helps to increase feeling of honor that government is taking care of them, increase their self-respect, financial independency, meet household expenditure, fulfillment of basic needs such as foods needs and purchase of health facilities and medicine. From this we can conclude that old age allowance plays a very important role in socio-economic wellbeing of the beneficiaries. Similarly, independent sample t-test shows that there is significant change in socio-economic wellbeing in education, and ethnic group. However, there is no any significant change in socio-economic wellbeing in gender, marital status, family type, size of family, occupation and monthly income of family of the respondents.